Analisis Data Panel Least Squares dan Panel ARDL terhadap Faktor-Faktor yang Mempengaruhi Angka Harapan Hidup di Indonesia tahun 2010-2024 - Muhammad Ryan Mahendra; Syamsurijal Tan; Yohanes Vyn Amzar (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
This study examines the effect of Gross Domestic Product (GDP), mean years of schooling, and poverty rate on life expectancy across 34 provinces in Indonesia during the period 2010–2024. The study employs panel data regression using the Random Effect Model (REM) and Panel Autoregressive Distributed Lag (Panel ARDL). The panel data regression results indicate that GDP and mean years of schooling have a positive and significant effect on life expectancy, while the poverty rate has a negative but insignificant effect. The Panel ARDL results show that in the short run, GDP has a positive and significant effect, mean years of schooling has a negative and significant effect, while the poverty rate has no significant effect on life expectancy. In the long run, GDP and the poverty rate have a negative and significant effect, whereas mean years of schooling has a positive and significant effect on life expectancy.